2003
DOI: 10.1074/jbc.m305701200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Thermotolerance in Mumps Virus-infected Cells Is Caused by Lack of HSP27 Induction Contributed by STAT-1

Abstract: Viral infection modulates the regulation of apoptosis in host cells. Here, we report a novel mechanism by which human cells infected with mumps virus become susceptible to apoptosis caused by extracellular stresses. Mumps virus stimulates proteasome-dependent degradation of STAT-1 by action of viral accessory protein V, resulting in a severe decrease in STAT-1 protein in infected cells. We exposed mumps virus-infected and uninfected cells to heat and chemical stress. The infected cells failed to acquire resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
0
18
1
1
Order By: Relevance
“…Hsp27 did not exhibit the same pattern of association in comparison to the other Hsp families, indicating different regulation mechanisms (Stephanou et al 1997;Cornelussen et al 2001;Yokota et al 2003). Indeed, Hsp27 levels did not alter considerably with the inflammatory indices.…”
Section: Discussioncontrasting
confidence: 55%
“…Hsp27 did not exhibit the same pattern of association in comparison to the other Hsp families, indicating different regulation mechanisms (Stephanou et al 1997;Cornelussen et al 2001;Yokota et al 2003). Indeed, Hsp27 levels did not alter considerably with the inflammatory indices.…”
Section: Discussioncontrasting
confidence: 55%
“…Human cells infected with virus such as mumps virus were recently shown to be more susceptible to apoptosis caused by extracellular stresses. The susceptibility is due to suppression of HSP27-dependent thermotolerance by the viral accessory protein V-mediated destruction of STAT-1 [188]. STAT-1 is required for transcriptional activation of the HSP27 gene, but not for the HSP70 gene, in addition to the activated HSF1 [188].…”
Section: Thermotolerancementioning
confidence: 99%
“…The susceptibility is due to suppression of HSP27-dependent thermotolerance by the viral accessory protein V-mediated destruction of STAT-1 [188]. STAT-1 is required for transcriptional activation of the HSP27 gene, but not for the HSP70 gene, in addition to the activated HSF1 [188]. HSP70 and HSP27 have also been implicated in translational thermotolerance; heat stress results in inhibition of general protein 18 H. G. Park et al Cellular responses to mild heat stress synthesis and in thermotolerant cells, protein synthesis is still rapidly inhibited by heat stress, but recovers faster than in naive heat-shocked cells, a phenomenon known as translational thermotolerance.…”
Section: Thermotolerancementioning
confidence: 99%
“…Finally, when intracellular HSP27 was neutralized by the internalized HSP27 antibody, the inhibition of UVBinduced apoptosis by arsenite condition was accordingly attenuated. Recently, Yokota et al (2003) infected cells with mumps virus to suppress HSP27, and they found that the infected cells that lacked HSP27 failed to acquire thermotolerance following exposure to the mild stresses.…”
Section: Discussionmentioning
confidence: 99%